Antimicrobial, Antioxidant, and α-Glucosidase-Inhibitory Activities of Prenylated p-Hydroxybenzoic Acid Derivatives from Oberonia ensiformis - Lu-Lu Wang; Wei Tang; Zhuo Wang; Yi-Xiang Wang; Ning Li; Fu-Cai Ren (Molecules)
Seven previously undescribed prenylated p-hydroxybenzoic acid derivatives, oberoniaensiformisins A–G, were isolated from an EtOH extract of the whole plant Oberonia ensiformis. Their structures were determined through spectroscopic analyses (IR, NMR) and HRESIMS analysis. The isolated compounds were tested for their antimicrobial, antioxidant, and α-glucosidase-inhibitory activity. Among them, compounds 6 and 12 exhibited potential antioxidant activity, while compounds 5, 6, 12, 13, and 15 showed varying degrees of α-glucosidase-inhibitory activity, with IC50 values ranging from 34.03 to 106.10 μg/mL.